2021
DOI: 10.1161/hypertensionaha.121.17164
|View full text |Cite
|
Sign up to set email alerts
|

In Aged Females, the Enhanced Pressor Response to Angiotensin II Is Attenuated By Estrogen Replacement via an Angiotensin Type 2 Receptor-Mediated Mechanism

Abstract: Loss of ovarian hormones following menopause contributes to the rise in cardiovascular risk with age. Estrogen plays a protective role against hypertension and end-organ damage by modulating the depressor actions of the AT 2 R (angiotensin type 2 receptor). Our aim was to determine whether estrogen replacement in aged female mice can lower arterial pressure, improve endothelial function, and reduce organ fibrosis via an AT 2 R-mediated mechanism. Mean arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This effect was associated with upregulation of renal AT2‐R, which was abrogated by AT2‐R antagonism. 39 In the present study, MHT and HFD upregulated mRNA expression of the Mas‐R and IL‐10, an antihypertensive cytokine, in the PVN of intact female offspring. Especially, the expression of AT2‐R was upregulated in HFD fed offspring of normotensive dams but not of hypertensive dams, suggesting that the effect of estrogen on the AT2‐R was impaired by MHT.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This effect was associated with upregulation of renal AT2‐R, which was abrogated by AT2‐R antagonism. 39 In the present study, MHT and HFD upregulated mRNA expression of the Mas‐R and IL‐10, an antihypertensive cytokine, in the PVN of intact female offspring. Especially, the expression of AT2‐R was upregulated in HFD fed offspring of normotensive dams but not of hypertensive dams, suggesting that the effect of estrogen on the AT2‐R was impaired by MHT.…”
Section: Discussionsupporting
confidence: 49%
“… 36 , 37 , 38 Another RAS antihypertensive pathway involving ANG II and the AT2‐R can also potentially mediate estrogen protection against ANG II– or aldosterone‐induced hypertension in female animals. 39 , 40 , 41 Estrogen replacement, in aged, reproductively senescent female mice, blunted the pressor response in an ANG II–induced model of hypertension. This effect was associated with upregulation of renal AT2‐R, which was abrogated by AT2‐R antagonism.…”
Section: Discussionmentioning
confidence: 95%
“…It has recently been demonstrated that Ang II-mediated pressor responses are ameliorated via angiotensin type 2 receptor (AT 2 R) activation in female but not male murine models [25,26]. Importantly, this depressor effect is lost with age and reproductive senescence and restored following oestrogen replacement [27]. This response was associated with the upregulation renal AT 2 R expression, suggesting that the modulation of blood pressure in this setting occurred via a AT2R-mediated renal mechanism.…”
Section: Sex Hormones Raas and Hypertensionmentioning
confidence: 99%
“…Using the four-core genotype model, where the Sry gene is translocated to chromosome 3, making it possible to differentiate between effects that are sex hormone and/or sex chromosome complement dependent ( Pessôa et al, 2015 ), it has been demonstrated that the X chromosome increases renal AT 2 receptor expression ( Dadam et al, 2017 ). Furthermore, numerous animal studies have demonstrated that renal AT 2 receptor expression is greater in females than in males ( Hilliard et al, 2014 ; Mirabito et al, 2014 ) and that this effect is linked to either estrogen, ovarian hormones, or reproductive status ( Mirabito et al, 2014 ; Barsha et al, 2021 ). Thus, the AT 2 receptor may contribute to the relative cardiorenal protection observed in adult females compared with age-matched males and reproductively senescent (e.g., postmenopausal) females.…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinsmentioning
confidence: 99%
“…There is evidence to suggest that the enhanced functional role of renal AT 2 receptors in females diminishes with age. In association with a reduction in renal AT 2 receptor expression, the chronic pressure-natriuresis relationship is shifted rightward ( Mirabito et al, 2014 ) and the hypertensive response to Ang II is enhanced ( Barsha et al, 2021 ) in aged reproductively senescent females compared with their adult counterparts. In these studies, genetic or pharmacological AT 2 receptor deficiency did not alter the response in the aged females.…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinsmentioning
confidence: 99%